Policy Analysis Approaches in Implementing the Ecological Engineering in Vietnam: Experiences from LEGATO – An Interdisciplinary Project - Trường, Đào Thanh; Anh, Nguyễn Thị Quỳnh; Anh, Nguyễn Thị Ngọc; Ly, Đặng Kim Khánh; Joachim, Spangenberg H.; Josef, Settele; Vera, Tekken; Beatriz, Rodríguez-Labajos (VNU Journal of Science: Policy and Management Studies; Vol 32 No 1, 2016)
Abstract: The paper examines the potential participations of stakeholder groups for applying the ecological engineering from policy approach. The focus here is on analyzing the demand of strenghthening sustainable linkages among the policy target group – policy implementing group – policy innovation group is most suitable solution to construct the ecological engineering application in rice cultivation in Vietnam. Unlike other projects, the diversity outputs and outcomes of LEGATO can provide  a huge neccessary sources from intersdisciplinary studies about the conditions for ecological engineering application in practice. Through policy analysis approach, authors identify the roadmap for policy preparing process of ecological engineering application within LEGATO for Kim Thanh district, Hai Duong province, Vietnam. There are four sections in this paper: (1) Policy paradigm and social construction (2) Policy approach and stakeholder involvement within LEGATO – an interdisciplinary  project (3) Policy analysis approaches in implementing LEGATO project (3) The role of key internal stakeholder groups in implementing the policy of ecological engineering application (4) Raising the participants of key internal stakeholder groups in implementing ecological engineering in Vietnam (case study in Kim Thanh district, Hai Duong province) and further steps in policy making process. Key words : interdisciplinary research, stakeholders, policy analysis approach, paradigm, policy making process